Sex modifies the renal consequences of high fructose consumption introduced after weaning - Monteiro, Letícia Maria; Barbosa, Celine Farias; Lichtenecker, Débora Conte Kimura; Argeri, Rogério; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2023)
After lactation, many children consume fructose-rich processed foods. However, overconsumption of these foods can predispose individuals to noncommunicable chronic diseases, which can have different repercussions depending on the sex. Thus, we evaluated the effects of fructose overload introduced after weaning on the renal function of young rats of both sexes. Methods: After weaning, male and female offspring of Wistar rats were assigned to drink water (the male/water and female/water groups) or 20% D-fructose solution (male/fructose and female/fructose groups). Food and water or fructose solution was offered ad libitum. Rats were evaluated at four months. Parameters analyzed: blood pressure, body weight, triglyceride levels, glomerular filtration rate, sodium, potassium, calcium, and magnesium excretion, macrophage infiltration, and eNOS and 8OHdG expression in renal tissue. CEUA-UNIFESP: 2757270117. Results: Fructose intake affected the blood pressure, body weight, and plasma triglyceride in all rats. Glomerular filtration rate was significantly reduced in males that received fructose when compared to that of the control group. Sodium and potassium excretion decreased in all fructose-treated rats; however, the excreted load of these ions was significantly higher in females than in males. In the female control group, calcium excretion was higher than that that of the male control group. Fructose overload increased magnesium excretion in females, and also increased macrophage infiltration and reduced eNOS expression in both males and females. Conclusions: Fructose overload introduced after weaning caused metabolic and renal changes in rats. Renal function was more affected in males; however, several significant alterations were also observed in the female-fructose group.